Carbon and nitrogen isotopic analysis of morphine from opium and heroin samples originating in the four major heroin producing regions. Issue 3 (12th December 2021) - Thompson, Robert A.; Morello, David R.; Panicker, Sini; Toske, Steven G.; Li, Li
Abstract: The forensic analysis of stable isotopes is a valuable tool to geo‐source natural or semisynthetic drugs such as cocaine and heroin. The present study describes a novel methodology to isolate morphine from opium for isotopic analysis. Furthermore, this isotopic data from regional sources is corroborated with morphine data obtained from seized heroin (deacetylated to morphine) from the same regions. All five primary alkaloids of opium, namely, morphine, codeine, thebaine, noscapine, and papaverine, were quantified using high performance liquid chromatography with photodiode array (PDA) detector before the preparative experiment to gather a complete major alkaloidal profile. Morphine fractions of authentic opium submissions from Mexico, South America, Southwest Asia, and Southeast Asia were isolated and collected using preparative high performance liquid chromatography, and the collected morphine samples were subsequently analyzed by isotope ratio mass spectrometry. Carbon and nitrogen isotope data are presented. The data demonstrate that nitrogen ratios are capable of differentiating samples from Mexico and South America while carbon ratios are able to distinguish Southwest Asian samples from other source regions. Analogous results have routinely been observed (as part of Heroin Signature Program analysis) for morphine obtained from deacetylated authentic heroin samples from the same source regions. The results suggest that the poppy growing region has a greater influence on the carbon and nitrogen isotope values than the heroin manufacturing processes employed. When utilized in conjunction with existing signature methodologies, carbon and nitrogen isotope ratio data can enhance the ability to geo‐source heroin. Abstract : Robust, reproducible, and precise methodology is presented to isolate morphine from opium samples via preparatory HPLC and its subsequent IRMS analysis to obtain carbon and nitrogen isotopic data. The results suggest that the poppy growing region has a greater influence on the carbon and nitrogen isotope values than the heroin manufacturing processes employed. When utilized in conjunction with existing signature methodologies, carbon and nitrogen isotope ratio data can enhance the ability to geo‐source heroin.